Desempenho, enzimologia e metabolismo de juvenis de pacu (Piaractus mesopotamicus) alimentados com dietas peletizadas e extrusadas com níveis médio e alto de lipídeos e carboidratos - Silva, Claucia Aparecida Honorato da (2008)
The purpose of this thesis was to study the biochemistry and metabolic adaptive aspects of pacu (Piaractus mesopotamicus) fed with different diets processing (extrusion or pelletization), wich had high or low levels of carbohydrates and lipids in their composition. It was analyzed growth and biochemical parameters: diet composition parameters, growth performance, efficiency of nutrient retention, filet fatty acids profile, transit velocity, digestibility of protein and energy, digestive enzymes (unspecific proteases trypsin, chymotrypsin, lipase, amylase and maltase), metabolic responses (glucose, lactate, piruvate, free fatty acids, free amino acids, glycogen, protein and ammonia) metabolic enzymes responses (ALAT, ASAT, GDH, LDH, MDH) and intestinal and liver morphology. We could observe that the different diets processing were affected by the levels of carbohydrates and lipids, where extrusion process showed high dependance of levels of carbohydrates. The zootechnical aproaches revealed protein sparing effect of carbohydrates in pelletized diets and, protein sparing effect of lipids in extruded diets. In relation to digestive enzymes responses it was observed that unspecific protease was induced by low lipids diet levels whereas amylase diminished its response in high lipids diet levels. The metabolic profile reflected different ways to get glucose available to the gluconeogenesis through different metabolic substrates, in order to support the energetic stores. The increase of both carbohydrates and lipids on different processing diets (extrusion or pelletization), support the morphological adaptations of liver and intestine of pacu, resulting in better nutrient absortion. In conclusion, the protein sparing effect may be found as much different carbohydrates and lipids combinations as different diet processing.